Using Metamodel Composition to Unify User Story and Use Case Metamodels - Amaral, Larissa Mangolim; Brandão, Anarosa Alves Franco; Siqueira, Fábio Levy (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
Requirements languages are often defined as metamodels for the standardization of a system’s requirements specification. The unification of these metamodels benefits general analysis and interoperability between requirements models. Even tough some authors already discuss systematic composition approaches, this application for requirements languages’ metamodels is still little explored. Therefore, we applied non-domain-specific composition frameworks to create a unified metamodel for User Story and Use Case diagram by assessing common points in related work. This application enabled reducing the subjectivity of the requirements languages composition process but still strongly depended on human curation.